Digital Storytelling in Elementary EFL Classrooms: Students’ Multidimensional Engagement and Teachers’ Pedagogical Challenges - Ni Made Ratminingsih; Luh Gede Eka Wahyuni; Made Hery Santosa (Universitas Hamzanwadi, 2026)
Digital storytelling has the potential to strengthen English literacy in EFL elementary classrooms by fostering meaningful student engagement. This study explores upper-grade elementary students’ perceptions of digital storytelling through cognitive, affective, and behavioral engagement, as well as teachers’ pedagogical challenges in its implementation. Using an interpretative phenomenological case study design, the study involved 21 students from Grades 4–6 and three English teachers at a public elementary school in North Bali, Indonesia. Data were collected through semi-structured interviews and analyzed using interpretative phenomenological analysis. The findings indicate that students perceived digital storytelling positively, showing developmental progression from basic linguistic understanding to higher-order engagement, increased motivation, active participation, and emerging learning transfer. Digital storytelling was perceived to support vocabulary learning, comprehension, and collaboration through multimodal learning experiences. However, teachers encountered pedagogical challenges related to content selection, preparation time, learner diversity, technological constraints, and classroom management. Despite these challenges, teachers demonstrated adaptive practices through scaffolding, peer tutoring, collaborative planning, and flexible use of digital resources. The study highlights the importance of teachers’ adaptive pedagogy in optimizing digital storytelling for English literacy development.